2011
DOI: 10.1186/1471-2164-12-176
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing analysis of the developing mouse brain reveals a novel microRNA

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs that can exert multilevel inhibition/repression at a post-transcriptional or protein synthesis level during disease or development. Characterisation of miRNAs in adult mammalian brains by deep sequencing has been reported previously. However, to date, no small RNA profiling of the developing brain has been undertaken using this method. We have performed deep sequencing and small RNA analysis of a developing (E15.5) mouse brain.ResultsWe identified the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 75 publications
12
57
0
Order By: Relevance
“…The predicted novel miRNAs exhibited much lower expression levels, consistent with the evidence that non-conserved miRNAs are often expressed at a lower level than conserved miRNAs [9799]. …”
Section: Discussionsupporting
confidence: 76%
“…The predicted novel miRNAs exhibited much lower expression levels, consistent with the evidence that non-conserved miRNAs are often expressed at a lower level than conserved miRNAs [9799]. …”
Section: Discussionsupporting
confidence: 76%
“…Previously they were found enriched in mammalian brain [Sempere et al, 2004;Linsen et al, 2010;Ling et al, 2011]. Other miRNAs, such as let-7a, miR-103 and miR-107, were also expressed abundantly, though not exclusively, in Atlantic halibut brain.…”
Section: Sex-biased Expression Of Conserved Mirnasmentioning
confidence: 98%
“…numbers of reads remained unmapped. However, a large proportion of deep sequencing data remains uncharacterized or discarded because of sequencing errors in model species [Morin et al, 2008;Ling et al, 2011]. SOLiD sequencing technology has an advantage over other similar technologies in discriminating single nucleotide polymorphisms from sequencing errors by interrogating each nucleotide in 2 different ligation steps.…”
Section: Deep Sequencing Of Atlantic Halibut Brain Andmentioning
confidence: 99%
“…The central nervous system is a rich source of miRNA expression [12], [13], [14], with a diversity of miRNA functions that affect many neuronal genes. A large number of miRNAs have been identified in the brain [12], [13], [14], [15], [16], [17], [18] including several miRNAs that are specifically expressed in glia cells and neurons [14], [19], [20]. Recent studies have shown that miRNA function is essential for the development of the zebrafish nervous system [21] and plays a role in neuronal plasticity in the rodent brain [7], [9].…”
Section: Introductionmentioning
confidence: 99%